2016
DOI: 10.1161/circinterventions.116.003785
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms and Neoatherosclerosis Patterns in Very Late Drug-Eluting and Bare-Metal Stent Thrombosis

Abstract: Background-There are few clinical studies on the pathophysiological mechanisms of very late stent thrombosis (VLST).We report optical coherence tomography findings in patients with VLST and compare the findings between bare-metal stents (BMS) and drug-eluting stents (DES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…OCT analysis in patients with DES‐ISR demonstrated a wide variety of abnormal findings, such as thin cap fibroatheroma‐containing neointima, in‐stent neointimal rupture, and intraluminal thrombi . Neoatherosclerosis has been reported to be more frequently observed and exhibit more longitudinal extension in BMS compared with DES . On the other hand, lipid‐rich neoatherosclerosis is considered to develop inside stents earlier in DES than BMS …”
Section: Discussionmentioning
confidence: 99%
“…OCT analysis in patients with DES‐ISR demonstrated a wide variety of abnormal findings, such as thin cap fibroatheroma‐containing neointima, in‐stent neointimal rupture, and intraluminal thrombi . Neoatherosclerosis has been reported to be more frequently observed and exhibit more longitudinal extension in BMS compared with DES . On the other hand, lipid‐rich neoatherosclerosis is considered to develop inside stents earlier in DES than BMS …”
Section: Discussionmentioning
confidence: 99%
“…Taniwaki et al reported that the mechanisms for VLST in 58 patients receiving DES (20 next‐ and 38 first‐generation) were malapposition (34.5%), neoatherosclerosis (27.6%), uncovered struts (12.1%), and stent underexpansion (6.9%) . Three other OCT studies also investigated the mechanisms of stent thrombosis but also included bare metal stent thrombosis or late DES thrombosis that might act as confounders . These studies were not performed exclusively with patients with very late DES thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, malapposition was consistently observed regardless of VLST 8 Three other OCT studies also investigated the mechanisms of stent thrombosis but also included bare metal stent thrombosis or late DES thrombosis that might act as confounders. 6,7,9 These studies were not performed exclusively with patients with very late DES thrombosis. The results of our study differed slightly from those of Taniwaki et al 8 in the types and frequencies of VLST mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthily, BMS and first-generation DES were designed to reduce the incidence of intra-stent restenosis (ISR) by delaying re-endothelization process up to 6-7 months in BMS and over 40 months in first-generation DES (sirolimus-and paclitaxeleluting stents) (Joner et al, 2006;Simard et al, 2014 (Yamaji et al, 2017). Especially neoatherosclerosis, defined as calcified or lipid neointima is another critical point to be considered as occurring more frequently and with increased longitudinal extension in BMS than DES occurring (Lee et al, 2013;Nakamura et al, 2016;Nakazawa et al, 2011). In line with this evidence, the pathophysiology of ISR and ISCT seems diametrically opposed.…”
Section: Intrastent Coronary Thrombosismentioning
confidence: 99%